Prinsip Sewa Dalam Perbankan Syariah: Analisis Akad Ijarah Dan Implementasinya Dalam Manajemen Perbankan Islam - Mega Rahmatia; Suci Rahmawati; Irwan Misbach (Multidisciplinary Journal of Religion and Social Sciences, 2026)
The lease principle in Islamic banking is a financing mechanism based on the ijarah contract, which is a contract for the transfer of usufructuary rights over goods or services through rental payments without the transfer of asset ownership. This concept places the benefits of goods or services as the object of the transaction, thus differing from the interest-based financing system in conventional banking. This study aims to analyze the concept of the ijarah contract in Islamic banking, examine the underlying sharia principles, and evaluate its implementation in Islamic banking management to support operational effectiveness, compliance with sharia principles, and the sustainability of Islamic financial institutions. The research method used is a literature study by examining various sources, such as fatwas from the National Sharia Council (DSN-MUI), related regulations, books, and scientific journals regarding the ijarah contract and ijarah muntahiyah bit tamlik (IMBT). The results of the study indicate that the implementation of the ijarah contract requires good asset management, fair risk sharing, clear contract separation, and supervision by the Sharia Supervisory Board to ensure compliance with sharia principles and the needs of modern society.